A UX evaluation approach for second-screen applications - Abreu, J. (2018)
Technological devices surrounding the television are changing, leading to changes in viewers’ habits and to the development of second-screen applications created to provide better TV viewing experiences. Used while watching television, the 2ndVision application presented in this paper is able to identify – through audio-fingerprint – content being displayed on the TV screen and present enhanced information on the second-screen. Under a participatory design approach, the development of the application took in consideration the users’ opinion regarding its main functionalities and interface solutions and included evaluation test sessions conducted in laboratory settings. This paper reports on the adopted UX evaluation approach where opinions regarding instrumental, non-instrumental and emotional impact of the application were collected with a combination of SUS, AttrakDiff and SAM scales. The results show that users experienced no major navigation problems and part of the iconography was validated. Considering the main goals of the application users were satisfied and interested in having such an application for providing additional information about the TV shows they watch. In addition the consistent variation of results between two sets of evaluation sessions, shows that the adopted UX evaluation approach is suitable to be used in a participatory design development of second-screen applications.